PHILOSOPHICAL EXPLORATION OF THE NATURE OF SPANDA IN SPANDA KARIKA - Kaur, Harsimran (Universal Research Reports, 2023)
‘Spanda Kārikā’ is composed by Vasugupta. It is a commentary on Śiva Sutra. Śiva Sutra is considered as revelation to Vasugupta. The reason for particularly taking ‘Spanda Kārikā’ instead of Śiva Sutra is that in Sutra, there is an emphasis on the Prakāsa aspect of the Divine, whereas in the ‘Spanda Kārikā’, the emphasis remains on the Vimarśa aspect of the Divine. So, the text appropriate for the study is ‘Spanda Kārikā,’ which presents active, dynamic, throbbing with life, creative pulsation. It must be noted that different words are used for the word Spanda depending on the context in which it is being used. Few words are Spanda Śakti, Svātantrya Śakti, Samvit Śakti, Vimarśa. To understand it correctly, let us discuss different definitions of Spanda in different texts.